Respuesta :
Answer:
x = 2
y = 5
Explanation:
x + y = 7; x − y = −3
Solve x+y=7 for x
x+y=7
x+y+−y=7+−y (Add -y to both sides)
x=−y+7
Step: Substitute−y+7 for x in x−y=−3:
x−y=−3
−y+7−y=−3
−2y+7=−3(Simplify both sides of the equation)
−2y+7+−7=−3+−7 (Add -7 to both sides)
−2y=−10
-2y/-2 = -10/-2
(Divide both sides by -2)
y=5
Step: Substitute 5 for y in x=−y+7:
x=−y+7
x=−5+7
x=2 (Simplify both sides of the equation)
Answer:
Step-by-step explanation:
First, line them up vertically.
x + y = 7
x - y = -3
Next add vertically.
x + x = 2x
y + (-y) = y - y = 0y
7 + (-3) = 7 - 3 = 4
Your equation should now read,
2x = 4
Divide both sides by 2 to solve for x
2x = 4
2 2
———-
x = 2
Lastly plug in 2 for x to solve for y. (It doesn’t matter which equation you use)
(2) + y = 7
-2 -2
y = 5